A comparative study of the Namibian and South African transitions to democracy and the effects on reconciliation - Mechnig, Christopher Markus (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Political Science))--University of Stellenbosch, 2010.